Morphological, functional and structural changes in red blood cells of type 2 diabetes patients with proliferative diabetic retinopathy and different diabetes duration (Ukrainian Journal of Ophthalmology, 2025)
Background: Hyperglycemia alters erythrocyte membrane properties, and the reduced Na+,K+-ATPase activity results in ionic imbalance and changes in size and osmotic resistance of red blood cells (RBCs), accelerates cell aging, and contributes to  impaired microvascular circulation.Purpose: To assess morphological, functional and structural changes in RBCs of type 2 diabetes patients with proliferative diabetic retinopathy (PDR) and different diabetes duration.Material and Methods: One hundred and six type 2 diabetes patients with PDR were included in the study. The control group (n=37) included volunteers without diabetes of age, gender and body-mass-index comparable to patients. Morphological and functional parameters of RBCs were determined using a MicroСС-20Рlus auto hematology analyzer (China). Percentages of hemolysis of erythrocytes in 0.1%; 0.2%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 1.0%, and 0.9% NaCl-buffer solutions were determined. We also determined mechanical chemolysis levels after centrifugation for 2 min and 4 min.Results: At 0.9% NaCl, osmotic hemolysis was 3.0-3.3-fold higher (р < 0.05) in PDR patients than in healthy individuals, but there was no significant difference in osmotic hemolysis between PDR patients with different durations of T2D. At 0.5% NaCl and 0.45% NaCl, PDR patients had percentages of hemolysis that were 3.5-4.0-fold higher (р < 0.05) and 2.0-2.5-fold higher (р < 0.05), respectively, than in controls. At 1.0% NaCl, there was a two-fold difference (р < 0.05) in RBC membrane resistance between patients and controls. In addition, patients with diabetes duration of 18 to 20 years were found to have erythrocytes with the highest resistance to damage. The percentages of hemolyzed RBCs after centrifuging for 2 min were 2.6 to 3-fold higher, and after centrifuging for 4 min, 3.0 to 3.75-fold higher, in patients relative to those in control subjectsConclusion: Compared to controls, patients with PDR exhibited signs of a relatively short residence time of RBCs in the circulation due to early cell membrane damage. The reduced structural resistance and loss of capability for effective perfusion in RBCs in the presence of PDR leads to a further impairment of microcirculation.
Keywords: osmotic; mechanical hemolysis; hyperglycemia; glycated hemoglobin; impaired microcirculation